An Evaluation of the Phenotypic Antibiotic Susceptibility of Potential Lactic Acid Bacteria Starter Cultures Isolated From Cambodian Fermented Foods - Ly, Dalin; Mayrhofer, Sigrid; Domig, Konrad J. (Frontiers in Food Science and Technology, 2022)
It is important to develop indigenous starter cultures for producing fermented foods that meet the expectations of Cambodians. These intentionally added cultures must be safe, including the absence of transferable antibiotic resistance (ABR). Thus, one of the first steps in considering the applicability of lactic acid bacteria (LAB) isolates as potential starter cultures should be the assessment of their ABR. Therefore, the antibiotic susceptibility of 46 LAB from Cambodian fermented foods was studied according to ISO 10932/IDF 233. The minimal inhibition concentrations (MICs) obtained were not only evaluated using differently defined breakpoints, but also MIC distributions and data from the scientific literature. - To avoid confusion with the classical Lactobacillus nomenclature generally applied in that literature, the former Lactobacillus (Lb.) names are still used here as an exception. - Applying only breakpoints would result in two Lb. pentosus, three Lb. futsaii, three Lb. namurensis and seven Pediococcus pentosaceus strains with acquired resistance (AR). However, considering further information, one Lb. futsaii, one Lb. fermentum and respectively three Lb. pentosus and Lb. namurensis strains would possess an AR. Although the correct assessment of AR in this study must be ensured by molecular methods, the critical evaluation will help in the comparison between phenotypic and genotypic data.